Study of major trauma of genitourinary system in patients referred to emergency center of Babol Shahid Beheshti Hospital, 1998-2003 - H Shafi (Babol University of Medical Sciences, 2006)
BACKGROUND AND OBJECTIVE: Trauma is a dynamic process and involves different systems of body according to its severity. Genitourinary system injury is seen in trauma process. This study was done to evaluate the major trauma of genitourinary system with special attention to multiple trauma patients.METHODS: This descriptive and cross-sectional study was performed on records of 293 patients with genitourinary system trauma who referred to emergency center of Shahid Beheshti hospital from 1998-2004. One hundred and two patients suffering from major trauma of genitourinary system who operated were included in this study. Then necessary information such as sex, age, pattern of trauma, type and mechanism of trauma, involved organ, clinical findings, associated lesions, surgical procedure, laboratory findings, duration of hospitalization and year of admission were obtained and studied.FINDINGS: From 102 patients, 92.2% were male and 7.8% were female with mean age of 29.4±13 years. 33.3% of patients had multiple trauma and 98% of them had blunt trauma. Mean duration of hospitalization was 6.2±4.4 days. From 13 patients (12.7%) with major kidney trauma, 5 cases had shattered kidney that went under nephrectomy. Only 1 patient (1%) had ureter trauma with final diagnosis of left middle ureter transection. Five patients (4.9%) had intraperitoneal rupture of bladder in which 3 cases had rupture in dome area. Five patients (49%) had urethral injury with clinical findings such as blood at meatus and inability to void. In 50 patients (49%) with penile trauma, 49 patients had penis Fx and 1 case had total amputation of penis and left testis. Fifteen patients (16.7%) had testis trauma in which clinical findings were pain, swelling and ecchymosis. Eleven patients (10.8%) had major trauma of scrotum.CONCLUSION: According to the results of this study, the most common organ involved in major trauma of genitourinary system was penis. Accurate history and complete physical examination should be considered in patients with multiple trauma.